Azacitidine induced lung injury: report and contemporary discussion on diagnosis and management - Alyamany, Ruah; Alnughmush, Ahmed; Almutlaq, Malak; Alyamany, Mohammed; Alfayez, Mansour (Frontiers in Oncology, 2024)
Azacitidine, a hypomethylating agent, has caused a paradigm shift in the outcomes of patients with myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) who are not eligible for stem cell transplantation, particularly in combination with BCL2 and IDH inhibitors.Azacitidine and Azacitidine-based combinations have been widely considered a safe lowintensity therapy when compared to traditional conventional treatments. The development of lung toxicity from azacitidine is not a well-characterized adverse event. However, if it happens, it can be fatal, especially if not recognized and treated promptly. In this review, we aim to familiarize the reader with the presentation of azacitidine-induced lung injury, provide our suggested approach to management based on our experience and the current understanding of its mechanism, and review the literature of 20 case reports available on this topic.